Reconsideration of Laparoscopic Cholecystectomy. (30th June 2011) - Kasuya, Kazuhiko; Itoi, Takao; Matsudo, Takaaki; Kyo, Bunsoh; Endo, Yasushi; Ikeda, Takahisa; Nagakawa, Yuichi; Suzuki, Yoshiaki; Shimazu, Motohide; Aoki, Tatsuya; Tsuchida, Akihiko
Abstract : We describe the surgical method of cases showing a distended gallbladder. Because the most important thing does not cause biliary tract injury, it is to find orientation carefully. The frequency of incidental gallbladder cancer was in 7 (0.7%) of the 983. Only cholecystectomy is necessary to be performed for Tis or T1 cancer, and surgery has to be changed to radical surgery for T2 cancer or deeper invasion. Laparoscopic cholecystectomy is already an established standard operation. In the presence of acute or severe chronic inflammation, special attention should be paid to these points.